Potential of New Bacterial Strains for a Multiproduct Bioprocess Application: A Case Study Using Isolates of Lactic Acid Bacteria from Pineapple Silage of Costa Rican Agro-Industrial Residues - Montero Zamora, Jéssica Pamela (2022)
Lactic acid bacteria (LAB) with potential for the development of multi-product processes are necessary for the valorization of side streams obtained during the biotechnological production of lactic acid (LA). In this study, 14 LAB strains isolated from pineapple agro-industrial residues in Costa Rica were cultivated in microplates, and the six strains with the highest growth were selected for fermentation in microbioreactors to evaluate the production of LA and acetic acid, and the consumption of glucose. Lacticaseibacillus paracasei 6710 and L. paracasei 6714 presented the highest OD600 values (1.600 and 1.602, respectively); however, the highest LA (in g/L) production was observed in L. paracasei 6714 (14.50 ± 0.20) and 6712 (14.67 ± 0.42). L. paracasei 6714 was selected for bioreactor fermentation and reached a maximum OD600 of 6.3062 ± 0.141, with a LA yield of 84.9% and a productivity of 1.06 g L−1 h −1 after 21 h of fermentation. Finally, lipoteichoic acid (LTA) detection from biomass was performed and the antimicrobial activity of the compounds present in the supernatant was studied. LTA was detected from L. paracasei 6714 biomass, and its supernatant caused significant inhibition of foodborne surrogate microorganisms. LAB isolated from pineapple silage have biotechnological potential for multiproduct processes.